Indonesia EVECTIVITY OF THE CLEAN WATER FILTRATION SYSTEM IN THE DISTRICT CITY WATER TREATMENT INSTALLATION (IPA IKK) PANDAN THORNS: EVEKTIVITAS SISTEM FILTRASI AIR BERSIH PADA INSTALASI PENGOLAHAN AIR IBU KOTA KECAMATAN (IPA IKK) PANDAN DURI - Wulandari, Fitriana Wulandari; muhammad iman, darmawan (Jurnal Teknologi Lingkungan, 2025)
The process of re-filtering or filtration of sample water in the IPA IKK Pandan Duri reservoir tank is due to the parameter levels that sometimes do not meet the quality standards according to PERMENKES No. 2 of 2023 concerning the Standards for Water Needs for Hygiene and Sanitation. Several factors causing the high levels of parameters in the water that has been filtered by the PDAM unit branch include, among others, the insufficient amount of filtration media used, corrosion in the filtration equipment (WTP), and/or the reservoir not being cleaned regularly. This leads to the filtered clean water becoming re-contaminated, so sometimes the clean water ready to be supplied to the communities in Desa Keruak and Jerowaru gets contaminated again. This research uses experimental research methods and descriptive analysis. Results obtained: pH levels experienced a concentration decrease of 0.22 mg/l with an effectiveness of 50.76%; NTU with a decrease of 12.44 mg/l with an effectiveness of 97%; TDS levels decreased by 315 mg/l with an effectiveness of 83.72%; Fe reduction was 0.963 mg/l with an effectiveness of 98%; lastly, the NO3 parameter with a decrease of 21.98 mg/l and the highest effectiveness reaching 99%.